Pendampingan Penyusunan Standar Porsi dan Siklus Menu Di Pondok Pesantren An-Nur Ar-Murtadlo Kecamatan Bululawang Kabupaten Malang - Hatijah, Nur; Nuswantari, Atika; Taufiqurrahman; Ratnasari, Devi Eka (Universitas Nusantara PGRI Kediri, 2021)
The students who live in the boarding school are those who are still in the stage of growth and development. Institutional food administration can be in the form of providing food to meet daily needs or to fulfill part of the daily nutritional needs such as breakfast, lunch, dinner, or snacks. The provision of food at Pondok Pesantren An Nur-2 Ar Murtadlo delivered in a simple way without any standard portions. This community service activity aims to gain understanding to partners about standard portions and preparation of menus in providing food for students so that their nutritional needs are met. The activity was carried out using educational methods as well as workshops on assisting the preparation of standard portions, menus and menu cycles. The results of educational activities are known by using a pre-post test questionnaire, it is known that education has succeeded in increasing the knowledge of participants (t test results = p = 0.0000 (<0.05). In addition, the skills are formed to compile standard portions, prepare menus and menus cycle 5 days and calculate the cost of shopping and practice the menu.